Atorvastatin Induces Mitochondria-Dependent Ferroptosis via the Modulation of Nrf2-xCT/GPx4 Axis - Zhang, Qi; Qu, Hang; Chen, Yinghui; Luo, Xueyang; Chen, Chong; Xiao, Bing; Ding, Xiaowei; Zhao, Pengjun; Lu, Yanan; Chen, Alex F.; Yu, Yu (Frontiers in Cell and Developmental Biology, 2022)
As one of the cornerstones of clinical cardiovascular disease treatment, statins have an extensive range of applications. However, statins commonly used have side reactions, especially the muscle-related symptoms (SAMS), ranging from muscle weakness, pain, cramps to severe condition of rhabdomyolysis. This undesirable muscular effect is one of the principal reasons for statin non-adherence and/or discontinuation, contributing to adverse cardiovascular outcomes. Moreover, the underlying mechanisms of muscle cells damage are still unclear. Here, we discovered that ferroptosis, a programmed iron-dependent cell death, serves as a mechanism in statins-induced myopathy. Among four candidates including atorvastatin, lovastatin, rosuvastatin and pravastatin, only atorvastatin could lead to ferroptosis in human cardiomyocytes (HCM) and murine skeletal muscle C2C12 cells (C2C12) instead of human umbilical vein endothelial cell (HUVEC). Atorvastatin inhibits HCM and C2C12 cell viability in a dose-dependent manner, accompanying with significantly augment in intracellular iron ions, reactive oxygen species (ROS) and lipid peroxidation. Further investigation noteworthily found that those alterations were particularly occurred in mitochondria and resulted in mitochondria dysfunction. Biomarkers of myocardial injury increase significantly during atorvastatin intervention as well. While, all of the above enhancement could be restrained by ferroptosis inhibitor. Mechanistically, GSH depletion, and the decrease of nuclear factor erythroid2-related factor 2 (Nrf2), glutathione peroxidase 4 (GPx4) and xCT cystine-glutamate antiporter (The main component is SLC7A11) involved in atorvastatin-induced muscular cell ferroptosis and damages. Downregulation of GPx4 in mitochondrial mediated ferroptosis signaling may be the core of it. In conclusion, our findings explore an innovative underlying pathophysiological mechanism of atorvastatin-induced myopathy and highlight that targeting ferroptosis serves as protective strategy for clinical application.